MENINGKATKAN DIGITAL LITERASI DAKWAH ISLAM BAGI PEREMPUAN: ANALISIS STRATEGI TUESDAY LOVE LETTER AIDA AZLIN MELALUI EMAIL SUBSCRIPTION: - - Latika Amatullah, Alysa (JURNAL ILMU BUDAYA, 2024)
Digital literature emerges as a phenomenon that reflects technological advancements, offering new ways to convey messages, values, and stories, particularly in the context of Islamic Da'wah. This research focuses on the utilization of email subscriptions as a tool for digital literacy, providing not only information and updates but also creating relevant content. The case study of Aida Azlin highlights how digital literature, through Tuesday Love Letters, captivates Muslim women with visual dramatization elements in her Da'wah activities. The analysis of four letters in December 2023 reveals five themes, incorporating the use of images, colors, emojis, typography, and downloadable images to enhance the reader's experience. The combination of compelling content and aesthetic design not only adds value in terms of additional income but also opens opportunities for the advancement and development of digital literature.